2018
DOI: 10.1038/s41598-018-26949-6
|View full text |Cite
|
Sign up to set email alerts
|

AKT signalling selectively regulates PINK1 mitophagy in SHSY5Y cells and human iPSC-derived neurons

Abstract: The discovery of mutations within genes associated with autosomal recessive Parkinson’s disease allowed for the identification of PINK1/Parkin regulated mitophagy as an important pathway for the removal of damaged mitochondria. While recent studies suggest that AKT-dependent signalling regulates Parkin recruitment to depolarised mitochondria, little is known as to whether this can also regulate PINK1 mitochondrial accumulation and downstream mitophagy. Here, we demonstrate that inhibition of AKT signalling dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 70 publications
5
45
0
Order By: Relevance
“…We identified a number of activators and inhibitors of ATG4B-mediated luciferase release (Supplementary File S5 ). We were particularly interested in AKT2 since AKT1 has previously been shown to be involved in autophagy and mitophagy ( Ni et al, 2018 ; Soutar et al, 2018 ). First, we transfected AKT2 in the ActinLC3dNGLUC reporter cell line, concomitantly with ULK1, a kinase we recently identified as a negative regulator of ATG4B activity and measured luciferase release ( Pengo et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a number of activators and inhibitors of ATG4B-mediated luciferase release (Supplementary File S5 ). We were particularly interested in AKT2 since AKT1 has previously been shown to be involved in autophagy and mitophagy ( Ni et al, 2018 ; Soutar et al, 2018 ). First, we transfected AKT2 in the ActinLC3dNGLUC reporter cell line, concomitantly with ULK1, a kinase we recently identified as a negative regulator of ATG4B activity and measured luciferase release ( Pengo et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, AKT2 is a novel gene that activates ATG4B, and promises to be an interesting candidate for future studies. The AKT family of proteins are known to regulate autophagosome formation and mitophagy ( Soutar et al, 2018 ), and AKT1 has recently been shown to directly phosphorylate ATG4B at Ser34 ( Ni et al, 2018 ). However, it has not been assessed whether this phosphorylation resulted in an increase or decrease of ATG4B activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous lines of evidence suggested the involvement of Akt/GSK3β signaling in CCCP-induced mitophagy [31] and in the elongation signals of MTs via EB1 activation [32]. Activated Akt functions through the phosphorylation and inhibition of Glycogen Synthase Kinase-3β (GSK3β) [33] leading to the activation of EB1-mediated MT synthesis through CLAPS2 recruitment.…”
Section: Resultsmentioning
confidence: 99%
“…Akt and GSK3β coordinately regulate the phosphorylation status of MT end capping molecules including CLASP2 and EB1, thus regulating their recruitment to the synthesis plus end of MTs[40]. Importantly, auto/mitophagy stimulating signal activate this pathway [31, 41]. The results of Western Blot analysis showed that the subacute oxidative stress significantly decreased the pAkt and GSK3β expression as compared to control cells (Fig.6-b, c), suggesting that subacute oxidative stress can affect MT synthesis by invoking signal resistance in PI3K/Akt/GSK3β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…POE SH-SY5Y cells were transfected with 100 nM siRNA and incubated for 72 h. Cell lysates were fractionated into cytoplasmic and mitochondria-enriched samples, and run on SDS-PAGE before IB with the Odyssey® CLx Imager (LI-COR Biosciences). Mitochondrial enrichment and Western blotting protocols were described previously 43 .…”
Section: Methodsmentioning
confidence: 99%